2007
DOI: 10.1177/0265407507079245
|View full text |Cite
|
Sign up to set email alerts
|

Feeling supported and feeling satisfied: How one partner's attachment style predicts the other partner's relationship experiences

Abstract: This study explored the association between one partner's attachment style and the other partner's relationship experiences (N = 305 couples). It was hypothesized that individuals would be more satisfied in their relationship when their partners were more secure (lower in attachment avoidance and anxiety), and that this association would be mediated by perceived caregiving. Results indicated that men were less satisfied when their female partners were higher in attachment anxiety, whereas women were less satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
97
4
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 28 publications
12
97
4
4
Order By: Relevance
“…Particularly for men, attachment anxiety in the partner relationship has found to be related with negative experiences and with lower overall relationship satisfaction (Collins & Read, 1990;Kane et al, 2007;Kirkpatrick & Davis, 1994;Simpson, 1990). In sum, there is some evidence that paternal separation anxiety is particularly relevant at the level of the marital relationship.…”
Section: Separation Anxiety In Family Relationshipsmentioning
confidence: 98%
“…Particularly for men, attachment anxiety in the partner relationship has found to be related with negative experiences and with lower overall relationship satisfaction (Collins & Read, 1990;Kane et al, 2007;Kirkpatrick & Davis, 1994;Simpson, 1990). In sum, there is some evidence that paternal separation anxiety is particularly relevant at the level of the marital relationship.…”
Section: Separation Anxiety In Family Relationshipsmentioning
confidence: 98%
“…For completeness, and because previous research has suggested mutual influence (Kane et al, 2007;Millings & Walsh, 2009), we included actor effects (e.g., from father's attachment to father's own caregiving), and all partner effects (e.g., from father's attachment to mother's caregiving). The model was simplified in a series of steps outlined below, in which a portion of the model was constrained and the reduction in model fit examined.…”
Section: Analytic Strategymentioning
confidence: 99%
“…Researchers have also explored the links between attachment orientation and responsive caregiving towards partner (e.g., Feeney & Collins, 2004;Kane et al, 2007;Kunce & Shaver, 1994;Millings & Walsh, 2009), and find that attachment security is linked with optimal partner caregiving. Attachment avoidance is associated with lower levels of caregiving generally (Carnelley, Pietromonaco, & Jaffe, 1996), and less responsive and more controlling caregiving specifically (Feeney & Collins, 2001), whereas attachment anxiety is also associated with less responsive caregiving, as well as less provision of instrumental support (Collins & Ford, 2010;Millings & Walsh, 2009).…”
mentioning
confidence: 99%
“…En este caso, nuestros datos no concuerdan con los hallados en otras investigaciones, en las que era la ansiedad de la mujer la que se asociaba de forma más clara con la menor calidad relacional percibida por el varón (Kane et al, 2007;Kirkpatrick y Davis, 1994). Aunque pueden ser múltiples las razones, nos parece posible pensar que en nuestro contexto, en el que se espera del varón una mayor fortaleza y seguridad, la mujer tenga una experiencia relacional más positiva con una pareja que se encuentra segura en la relación y, que por el contario, la inseguridad del varón y la continua necesidad de reaseguración, típica de la persona más ambivalente, pueda hacer que ellas se sientan más a disgusto.…”
Section: Discussionunclassified